Ratio Analysis to Measuring Financial Performance of PT. Indosat Tbk. Listed in IDX (Period 2015-2018) - Eva Putri Priari; Ani Wulandari (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2019)
A company's health assessment can be done by analyzing the financial statements to Determine the performance of its finances. One of the analytical tools that can be used is the analysis of financial ratios. This research aims to analyze the financial performance of PT. Indosat Tbk. Is reviewed restaurants from the financial ratio analysis. The methods used are the data analysis using descriptive qualitative measurements liquidity ratio, solvency, profitability, and activity. The results Showed that the financial performance of PT. Indosat Tbk. Based on the overall liquidity ratio of the company in a good condition (liquid). The overall solvency ratio of the company is said to be solvable or in good condition to guarantee its debts. The company's profitability ratio is at a less than good position (inefficient). While at the ratio of its activity the company is said to be less efficient.